Aortic root valve‐sparing repair and dissections in Marfans syndrome during pregnancy: A case series. Issue 7 (5th May 2020) - Cottrell, Jesse; Calhoun, John; Szczepanski, Jamie; Corvera, Joel; Creswell, Lawrence L.; Kogon, Brian; Hasaniya, Nahidh; Copeland, Hannah
Abstract: Introduction: Marfan syndrome is a connective tissue disorder caused by mutations in the fibrillar FBN‐1 gene. Aortic dissection and rupture are major causes of morbidity and mortality and are of special concern during pregnancy. Materials and Methods: The authors report four cases of aortic root repair with preservation of the native aortic valve that have has created a discussion between cardiothoracic surgeons, obstetricians, and gynecologists regarding the best care for Marfan syndrome patients. We present these cases here with a review of the literature. Results: Surgery of the aorta and valves in Marfan syndrome is less risky than in previous eras and surgical management guidelines are generally accepted. Yet, we may be unnecessarily referring women to terminate pregnancies or to avoid pregnancy. We believe there may be alternative options for these patients. Conclusions: Marfan syndrome during pregnancy can be navigated with preconception counseling, antepartum care, and close postpartum follow‐up involving an appropriate multidisciplinary team.